Emil Lask. W stulecie śmierci - Noras, Andrzej J. (Folia Philosophica, 2018)
The present article concentrates on depicting the main elements of Emil Lask’s philosophy, a distinguished Neo-Kantianist who, simultaneously, may be regarded as Heidegger’s teacher. The meaning of Lask’s work comes down to several issues, although in this article two of them have been emphasised: first, Kant should not be read in the light of Fichte’s philosophy; second, in Lask’s philosophy the primacy of practical reason in logic, characteristic for the Baden Neo-Kantianism, is questioned. In Lask’s understanding, the logic of philosophy which is the critical theory of cognition derives from the critical consideration over the Baden Neo-Kantianism.